Seni Berpidato dalam Pemikiran Socrates, Plato, dan Aristoteles: Analisis Pidato Soekarno 1 Juni 1945 - Veranita, Astrid (Aqidah-Ta: Jurnal Ilmu Aqidah, 2025)
The thoughts of Socrates, Plato and Aristotle are interrelated in developing theories about rhetoric. The results of the study show that First, Socrates, Plato, and Aristotle criticized the sophists using persuasion and coaxing to win public debates, so that by all means they were able to persuade the majority of Athenian citizens to make a decision. Second, Socrates, Plato, and Aristotle tried to create a rhetoric that prioritized ethics and logic in achieving a truth. Third, Socrates’ dialectic has fostered the critical attitudes and abilities of Athenian citizens, inspiring Plato and Aristotle to develop a theory of rhetoric. The implication of this study is that rhetoric must be based on ethics and logic so as to direct the majority of citizens to think critically, logically and based on the values ​​of virtue and goodness. Thus, the decision of the majority of citizens is not a decision that will be regretted in history, but is a wise decision with full critical, logical and ethical thinking.